The potencial effect of non-transparent lobbying on competitiveness through economic freedom in the EU – An empirical survey - Laboutková, Šárka; Staňková, Lucie (Univerzita Pardubice, 2016)
The competitive strength of individual countries is not only affected by their economic efficiency and productiveness, there is also a broad range of other socio-economic and political factors that includes institutional quality. Crucial factors influencing institutional quality are transparency and the scope of civil and economic liberties. It should be easy to scrutinize how decisions are made, the influences behind them and how taxpayer’s money is allocated. On the other side the plurality of interests is a necessary prerequisite and starting point for a free and open society. The lobbying and consultancy industry is a natural, important and legitimate part of the democratic decision-making process, however sometimes lobbying practices go beyond the legitimate representation of interests, and methods are deceptive. This kind of behavior is usually non-transparent and unfairly influences political processes, generating the potential for corrupt practices and excessive regulation of economic activities negatively influencing economic freedom and thus the competitiveness. The aim of the article is to prove the significant effect between economic freedom and competitiveness within the European Union countries based on an analysis of two indexes – the Economic Freedom Index and the Global Competitiveness Index. A direct and fairly strong dependence was proved.
Keywords: competitiveness; economic freedom; European Union; lobbying; transparency; regulation; E610; K40; O170; P48